Optimisation of PEDOT coating on PCL for bone tissue engineering - Chua, Wai Jie (2019)
Bone tissue engineering involves the combination of a biomaterial scaffold, cells and growth factors to regenerate damaged tissues. These scaffolds act as temporary matrix providing the right environment and architecture for bone tissue to grow and develop. Throughout the years, there has been an increasing interest in using electrical stimulation to improve bone tissue engineering. Since then, numerous types of electroactive scaffolds for electrical stimulation have emerged. Vapour phase polymerization (VPP) was used by Iandolo et. al to deposit a poly(3,4ethylenedioxythiophene) tosylate (PEDOT: Tos) coating on polycaprolactone (PCL) to produce an electroactive scaffold for bone tissue engineering. However, the adhesion of such a coating was too low and unsatisfactory for actual applications. Thus, as an extension of previous research, this project aims to improve the adhesion of PEDOT:Tos to PCL via crosslinking with (3-glycidyloxypropyl)trimethoxysilane (GOPS). The coatings were then characterized with ATR-FTIR, SEM, contact angle measurement, scotch tape test, 4-point probe and cyclic voltammetry. It was found that crosslinked PEDOT:Tos coatings had lower conductivity, smaller pores in their morphology, larger thicknesses and similar electrochemical properties compared to those without crosslinks. The adhesion of 10%v/v GOPS was found to be much higher than the coating without GOPS using the peel test. The crosslinked PEDOT:Tos successfully improved the adhesion of PEDOT:Tos coatings and has potential for future application in bone tissue engineering.